Effectiveness of performance measurement in hybrid organizations A systematic literature review - Ekaristi, Clara Yully Diana; Utomo, Dwi Cahyo; Rohman, Abdul (Edelweiss Applied Science and Technology, 2025)
This study investigates how performance measurement operates within hybrid organizations that balance competing institutional logics, stakeholder expectations, and regulatory demands. It aims to identify the key determinants influencing the effectiveness of performance measurement systems and propose a context-sensitive conceptual framework. A systematic literature review (SLR) was conducted using the Scopus and Web of Science databases, focusing on publications from 2020 to 2024. Thirty peer-reviewed studies were examined through a three-tiered coding process to classify the critical factors and emerging trends that shape performance measurement effectiveness. The review identifies four interrelated dimensions that collectively influence the reliability of performance measurement: governance structure, technical challenges, stakeholder engagement, and institutional dynamics. Persistent issues, such as fragmented accountability, inconsistent reporting, and regulatory rigidity, continue to hinder effective evaluations. An integrated, data-driven, and contextually grounded framework is required to strengthen adaptability, transparency, and stakeholder trust in hybrid performance measurement systems. This study offers actionable insights for policymakers, managers, and scholars to design more reliable, technologically enabled, and stakeholder-inclusive performance measurement models for hybrid organizations.